Tourism in Poland following EU entry - Kapera, Izabela (Bulletin of Geography. Socio-economic Series, 2013)
The aim of this study was to examine how tourism developed in Poland following EU entry. A particularly large increase in local government spending on tourism and foreign tourist expenditures have been observed for the study period in Poland. An increase in passenger volume at Polish airports has also been observed. Among the many factors influencing the situation in the domestic tourism market, regulations relating to EU entry and the inflow of grants from the EU were of leading importance. At the same time, Poland’s entry into the EU may accelerate some change processes, the effects of which may be observed in the future.